2000
DOI: 10.1108/eb028909
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transformational Leadership on Subordinate Motivation, Empowering Norms, and Organizational Productivity

Abstract: As part of an integrative model of leadership, transformational (versus transactional) styles are proposed to be related to subordinates' motivation and commitment to quality, the strength of empowering norms at the subunit level, and organizational productivity. Transformational and transactional styles also are proposed to be related to the self-image of leaders. Hypotheses are tested in a military setting, the United States Army Recruiting Command, through the use of survey data provided by mid-level lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
128
0
16

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 43 publications
11
128
0
16
Order By: Relevance
“…As a result, followers trust the leader and are motivated to do more than originally expected to do (Yukl, 2002). Several empirical studies have demonstrated the positive impact of transformational leadership on follower motivation, commitment and empowerment (Bass & Avolio, 1990;Berson, Shamir, Avolio, & Popper, 2001;Masi & Cooke, 2000).…”
Section: Charismatic and Transformational Leadershipmentioning
confidence: 99%
“…As a result, followers trust the leader and are motivated to do more than originally expected to do (Yukl, 2002). Several empirical studies have demonstrated the positive impact of transformational leadership on follower motivation, commitment and empowerment (Bass & Avolio, 1990;Berson, Shamir, Avolio, & Popper, 2001;Masi & Cooke, 2000).…”
Section: Charismatic and Transformational Leadershipmentioning
confidence: 99%
“…Nowadays scientists Howell, Neufeld, & Avolio, 2005;Quijano et al, 2007) are working on the applicability of leadership concepts to organizational life (e.g. House, Hanges, Javidan, Dorfman, & Gupta, 2004;Masi & Cooke, 2000;Molero, Cuadrado, Navas, & Morales, 2007). This is also supported by the scientist-practitioner-model, developed by the European Network of Organisational Psychology (ENOP) (ENOP, 1998).…”
mentioning
confidence: 99%
“…In this regard, collegiality appears to play an imperative role in leveraging the de facto superordinate-subordinate relationship as this investigation unfolded. By providing team members with resources needed and empowering them to take responsibilities (Masi, 2000), the team lead or manager is likely to build an esprit-de-corps team and ensure collective advancement.…”
Section: Discussionmentioning
confidence: 99%